Update of treatment algorithms for Clostridium difficile infection. (May 2018) - Ooijevaar, R.E.; van Beurden, Y.H.; Terveer, E.M.; Goorhuis, A.; Bauer, M.P.; Keller, J.J.; Mulder, C.J.J.; Kuijper, E.J.
Abstract: Background: Clostridium difficile is the leading cause of antibiotic-associated diarrhoea, both in healthcare facilities and in the community. The recurrence rate of C. difficile infection (CDI) remains high, up to 20%. Since the publication of the European Society of Clinical Microbiology and Infectious Diseases (ESCMID) guidance document on CDI treatment in 2014, new therapeutic approaches have been developed and tested to achieve higher sustained clinical cure in CDI. Aim: To review novel treatments and approaches for CDI, except probiotics and vaccines. We focused on new antibiotics, antibiotic inactivators, monoclonal antibodies and gut microbiota modulating therapies. Sources: A literature review was performed for clinical trials published in PubMed, Embase or Cochrane Library between January 2013 and November 2017. Content: We analysed 28 clinical trials and identified 14 novel agents. Completed phase 2 studies were found for cadazolid, LFF571, ridinilazole and nontoxigenic C. difficile strains. Four phase 3 active comparator studies comparing vancomycin with bezlotoxumab, surotomycin ( n  = 2) and rifaximin have been published. Seven clinical trials for treatment of multiple recurrent CDI with faecal microbiota transplantation were analysed, describing faecal microbiota transplantation by upper or lower gastrointestinal route ( n  = 5) or by capsules ( n  = 2). Implications: Metronidazole is mentioned in the ESCMID guideline as first-line therapy, but we propose that oral vancomycin will become the first choice when antibiotic treatment for CDI is necessary. Fidaxomicin is a good alternative, especially in patients at risk of relapse. Vancomycin combined with faecal microbiota transplantation remains the primary therapy for multiple recurrent CDI. We anticipate that new medication that protects the gut microbiota will be further developed and tested to prevent CDI during antibiotic therapy.